1997
DOI: 10.1103/physreve.56.6719
|View full text |Cite
|
Sign up to set email alerts
|

Fokker-Planck equation for the energy cascade in turbulence

Abstract: We present a detailed analysis of the energy dissipation averaged over a distance r,⑀ r , in terms of a stochastic process through scales. Using experimental data recorded in a low temperature helium jet, we give evidence that the probability density function of ln(⑀ r) obeys a Fokker-Planck equation. The drift and diffusion coefficients are calculated directly from the data. The drift is linear in ln(⑀ r) and the diffusion is constant. With these coefficients, the equation can be solved exactly, giving a Gaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
73
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(85 citation statements)
references
References 11 publications
12
73
0
Order By: Relevance
“…In a series of recent papers, Friedrich, Peinke and collaborators [40,41,42] have experimentally shown that, for a fixed position, the velocity or dissipation statistics in turbulence are Markov processes. Their Fokker-Planck approach can be shown to be linked (in case of lognormal cascades) to Castaing's semi-group decomposition approach [38,39,36].…”
Section: Semigroup Composition Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of recent papers, Friedrich, Peinke and collaborators [40,41,42] have experimentally shown that, for a fixed position, the velocity or dissipation statistics in turbulence are Markov processes. Their Fokker-Planck approach can be shown to be linked (in case of lognormal cascades) to Castaing's semi-group decomposition approach [38,39,36].…”
Section: Semigroup Composition Propertiesmentioning
confidence: 99%
“…Our results can be compared to previous studies, some of them done in purely experimental grounds. Let us first note that in some cases (see [41]) the study is done considering a Fokker-Planck equation with drift and diffusion coefficients D 1 and D 2 . The associated stochastic differential equation (Langevin form) is:…”
Section: Differential Properties and A Langevin Equationmentioning
confidence: 99%
“…This method is definitely more general than the above mentioned analysis by structure functions, which characterize only the simple scale statistics p(u(r)) or p(v(r)). The Fokker-Planck method has attracted interest and was applied to different problems of the complexity of turbulence like energy dissipation [23,24,25], universality turbulence [26] and others [11,27,28,29,30,31]. The Fokker-Planck equation (here written for vector quantities) reads as…”
mentioning
confidence: 99%
“…While this scheme is simple, it has previously played a decisive role in explaining scale-correlations for observed multiplier distributions [3,4] and observed Markov properties [8,9]. For two-point statistics with constant bin-bin distance d < L/η, the appropriate averaging is given by…”
mentioning
confidence: 99%
“…The second complication arises because experimental cumulants are derived from measured moments rather than the other way round [6], requiring translational averaging over two-point moments rather than two-point cumulants for theory also. The proper procedure is hence to convert theoretical cumulants (8) to moments, average these to restore translational invariance, and then convert them back to translationally invariant cumulants for experimental comparison.…”
mentioning
confidence: 99%